2008
DOI: 10.1002/ejoc.200701174
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Annulenes via Multiple Wittig Reactions; In‐Situ Dimerization of 1,2;5,6‐Dibenzocyclooctatetraene

Abstract: A simple synthetic route to tetrabenzo [16]-and hexabenzo-[24]annulene systems using one-pot multiple Wittig reactions is presented. We report the characterization of the all-transisomer of tetrabenzo [16]annulene by NMR spectroscopy and X-ray diffraction. Several isomers of an unexpected, tetra-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This reaction has been employed on several occasions in the synthesis of DBCOT itself or derivatives thereof. [ 39–45 ] Unsubstituted DBCOT 2 , for instance, was synthesized through Wittig reaction already in the 1960s. [ 39,40 ] Our first two synthetic routes therefore make use of this reaction (Scheme 1a,b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction has been employed on several occasions in the synthesis of DBCOT itself or derivatives thereof. [ 39–45 ] Unsubstituted DBCOT 2 , for instance, was synthesized through Wittig reaction already in the 1960s. [ 39,40 ] Our first two synthetic routes therefore make use of this reaction (Scheme 1a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The reason for its formation is the low stereoselectivity ( cis or trans ) of the Wittig reaction. In 2008, Herges [ 42 ] and Nuckolls [ 41 ] independently reported that the double Wittig reaction between o ‐phthaldehyde ( 12 ) and the 1,2‐bis(triphenylphosphonium ylide) 13 proceeded via the corresponding cis , trans ‐derivative of 2 . This highly reactive species with a calculated strain energy of 18 kcal mol −1[ 41 ] immediately underwent further reactions or decomposed, diminishing the yield of the cis , cis ‐derivative 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The ligands (4-spy, 4-(2-npy) and 4-npy) were prepared from a previously reported method. 28 Ligands H 2 oba and other metal salts are obtained commercially and used without further purification. Elemental analyses (C, H, and N) were performed using a PE 2400 II elemental analyzer.…”
Section: Methodsmentioning
confidence: 99%